Calcineurin: A Poorly Understood Regulator of Muscle Mass - Hudson, Matthew B. (2013)
This review will discuss the existing literature that has examined the role of calcineurin (CnA) in the regulation of skeletal muscle mass in conditions associated with hypertrophic growth or atrophy. Muscle mass is determined by the balance between protein synthesis and degradation which is controlled by a number of intracellular signaling pathways, most notably the insulin/IGF/phosphatidylinositol 3-kinase (PI3K)/Akt system. Despite being activated by IGF-1 and having well-described functions in the determination of muscle fiber phenotypes, calcineurin (CnA), a Ca(2+)-activated serine/threonine phosphatase, and its downstream signaling partners have garnered little attention as a regulator of muscle mass. Compared to other signaling pathways, the relatively few studies that have examined the role of CnA in the regulation of muscle size have produced discordant results. The reasons for these differences is not obvious but may be due to the selective nature of the genetic models studied, fluctuations in the endogenous level of CnA activity in various muscles, and the variable use of CnA inhibitors to inhibit CnA signaling. Despite the inconsistent nature of the outcomes, there is sufficient direct and indirect evidence to conclude that CnA plays a role in the regulation of skeletal muscle mass.